CC2 Does mycoplasma genitalium cause proctitis? A case report. (30th June 2016) - Finnerty, Fionnuala; Pinto-Sander, Nicolas; Richardson, Daniel
Abstract : Background/introduction: Mycoplasma genitalium is an emerging sexually transmitted pathogen implicated in urethritis in men and cervicitis and pelvic inflammatory disease in women. The overall prevalence of rectal mycoplasma genitalium was 4.4% in one study of MSM. However, symptomatic disease is not well reported. Aims/objectives: We describe a case of symptomatic rectal mycoplasma genitalium Methods: Retrospective case not review Results: A 19 year old MSM attended with a 2 week history of rectal bleeding, discharge and tenesmus. His last sexual contact was 6 weeks previously: condom-less receptive anal intercourse. On examination, he had no lymphadenopathy, no rash and no evidence of oral ulceration. On proctoscopy, he had erythematous mucosa and multiple small discrete rectal ulcers. Triple site swabs were taken including gonorrhoea culture, rectal swab for LGV and multiplex PCR (syphilis, HSV and mycoplasma genitalium). A full blood borne virus screen was performed. He was treated with ceftriaxone (500 g IM), azithromycin (1 g PO), doxycycline (100 mg PO BD for 7 days) and acyclovir (400 mg PO TDS for 5 days) but his symptoms did not resolve. All tests were negative except rectal multiplex PCR was positive for mycoplasma genitalium. He was diagnosed as having symptomatic mycoplasma genitalium infection and was treated with a prolonged course of azithromycin. His symptoms subsided. Discussion/conclusion: Mycoplasma genitalium has been found in the rectum of MSM and is usually asymptomatic. We describe a case of proctitis which seems to be related to Mycoplasma genitalium. MSM with unresolved proctitis should be tested for Mycoplasma genitalium.